PENGARUH MODEL PEMBELAJARAN KOOPERATIF ROLE PLAYING TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN BAHASA INDONESIA KELAS IV SD - Sundari, Wulan; Muhammad Taheri Akbar; Susanti Faipri Selegi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is limited to the cooperative role playing learning model for fourth grade students in Indonesian language subject chapter 3, look around at SD Negeri 143 Palembang. Based on the problem formulation above, the aim of this research is as follows: "to find out the effect of the role playing cooperative learning model on the eyes Indonesian language lessons ". The research method used in this research is the true experimental method, namely research carried out in two classes, namely the experimental class and the control class as a comparison class. The data collection techniques used in this research are tests and documentation. Based on the results of research in the application of the Cooperative Role Playing learning model, calculation results were obtained through hypothesis testing using the Independent Sample t-test where tcount = 2.142 and ttable = 2.021 and the value is significant 2-tailed is 0.025. Thus, there is an influence in the application of the Cooperative Role Playing learning model on student learning outcomes in class IV Indonesian at SD Negeri 143 Palembang.